Lagerungstechniken in der Urologie: Tipps und Tricks = Surgical positioning techniques in urology : tips and tricks - Miernik, Arkadiusz; Häcker, Axel (Der Urologe, 2017)
Correct positioning of patients during preoperative preparations is essential for success of the intervention to avoid any positioning trauma and to provide the best access to the targeted structures. The appropriate positioning (and optimal performance) means that complications are avoided and also makes an essential contribution to the smooth course of the surgical intervention. A correct position is essential particularly in urology because the organs assigned to the discipline of urology are anatomically mostly difficult to reach. A further important function of the correct positioning technique is the avoidance of injuries to the patient. This article summarizes the most common positioning techniques in urological interventions with special emphasis on the explanation of practical advice, helpful tips and possible complications that can enable even junior surgeons to correctly perform the appropriate positioning technique.